IMPLEMENTATION ANALYSIS OF PUBLIC INFORMATION DISCLOSURE POLICY: A CASE STUDY OF THE FOREST MANAGEMENT TECHNICAL PERSONEL INFORMATION SYSTEM (THE SIGANISHUT) - Dwi Septina, Ane; Rianti, Anita; Iqbal, Mohamad; Sihombing, Vivin Silvaliandra; Rahmayanti, Atika Zahra (Association of Indonesian Forestry and Environment Researchers and Technicians, 2025)
The analysis of public information disclosure policy implementation is a crucial step in improving services and providing strategic references for government public information programs. The Forest Management Technical Personnel Information System (SIGANISHUT) was developed under the Ministry of Environment and Forestry (MoEF) Regulation No. 8 of 2021. This study examined the implementation of public information disclosure within SIGANISHUT, which is managed by the Directorate of Fees and Forest Product Distribution, Directorate General of Sustainable Forest Management. Using qualitative methods—including in-depth interviews, literature reviews, and observations—this study found that SIGANISHUT is managed with a user-centered approach. However, challenges persist regarding resource availability and disposition. The system requires additional personnel and increased budget allocation to support field-level policy socialization. Despite these challenges, policy implementers demonstrate accountability in implementing MoEF Regulation No. 8 of 2021 and respond effectively to user complaints and operational issues. From a bureaucratic perspective, the current framework adheres to the Standard Operating Procedures outlined in the regulation, with a well-coordinated division of responsibilities among implementers. SIGANISHUT streamlines bureaucracy by reducing service times through digital integration.With sufficient support and well-designed policies, the legislative mandate on public information disclosure can be implemented more effectively and efficiently. This study underscores the importance of continuous evaluation and development to ensure SIGANISHUT meets stakeholder expectations and contributes to transparency and accountability in sustainable forest management.